International Conference on Mobile Business (ICMB'05)
DOI: 10.1109/icmb.2005.47
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors and Facilitators for Mobile Payment Adoption in Australia: A Preliminary Study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 2 publications
2
31
0
2
Order By: Relevance
“…Surprisingly, we identified only four papers focusing exclusively on merchants. Three of them uncovered the various barriers to the merchant adoption [54,83,78]. Researchers found barriers such as high costs (transaction fees), complexity (ease of use), lack of relative advantage, low compatibility, and the interdependence between consumers and merchants at an early stage of development.…”
Section: Merchant Powermentioning
confidence: 99%
“…Surprisingly, we identified only four papers focusing exclusively on merchants. Three of them uncovered the various barriers to the merchant adoption [54,83,78]. Researchers found barriers such as high costs (transaction fees), complexity (ease of use), lack of relative advantage, low compatibility, and the interdependence between consumers and merchants at an early stage of development.…”
Section: Merchant Powermentioning
confidence: 99%
“…As summarised in [19] the demand side of mPayment (customers and end-users) has been studied empirically and qualitatively through models such as TAM (Technology Acceptance Model) and TTF (Task-Technology Fit), including participants from a country or a region [3], [8], [11], [14][15], [25][26][27][28][29][30]. These studies have identified a number of mPayment factors influencing negatively or positively customer adoption and use (Figure 2).…”
Section: Mpayment Adoption and Acceptancementioning
confidence: 99%
“…The customer subgroups in the table refer to the target groups of mCommerce customers, and to customers who use contactless payment for traditional or innovative services [11]. Customers have been found to be willing to accept mPayment services depending on the context of the offer but have not created a strong demand for them [8][9], [11], [13][14][15], [17].…”
Section: Mobile Payment Stakeholder Groupsmentioning
confidence: 99%
See 2 more Smart Citations